Future of an “Asymptomatic” T-cell Epitope-Based Therapeutic Herpes Simplex Vaccine - Dervillez, Xavier (2012)
Considering the limited success of the recent herpes clinical vaccine trial [1], new vaccine strategies are needed. Infections with herpes simplex virus type 1 and type 2 (HSV-1 & HSV-2) in the majority of men and women are usually asymptomatic and results in lifelong viral latency in neurons of sensory ganglia (SG). However, in a minority of men and women HSV spontaneous reactivation can cause recurrent disease (i.e., symptomatic individuals). Our recent findings show that T cells from symptomatic and asymptomatic men and women (i.e. those with and without recurrences, respectively) recognize different herpes epitopes. This finding breaks new ground and opens new doors to assess a new vaccine strategy: mucosal immunization with HSV-1 & HSV-2 epitopes that induce strong in vitro CD4 and CD8 T cell responses from PBMC derived from asymptomatic men and women (designated here as “asymptomatic” protective epitopes”) could boost local and systemic “natural” protective immunity, induced by wild-type infection. Here we highlight the rationale and the future of our emerging “asymptomatic” T cell epitope-based mucosal vaccine strategy to decrease recurrent herpetic disease.